Surgical treatment of primary hyperparathyroidism in the elderly. Issue 6229 (14th June 1980) - Heath, D A; Wright, A D; Barnes, A D; Oates, G D; Dorricott, N J
Abstract : Twelve patients aged over 70 with primary hyperparathyroidism (persistent hypercalcaemia and raised serum parathyroid hormone concentrations) underwent parathyroidectomy, which was well tolerated by all. After operation serum calcium concentrations returned to normal and the commonest symptoms before operation (muscle weakness, malaise, and mild to severe dementia), although not related in severity to the degree of hypercalcaemia, improved. Mental function was greatly improved. The findings suggest that primary hyperparathyroidism should be sought in any elderly patient with hypercalcaemia and that more such patients with the diagnosis should be considered for parathyroidectomy irrespective of age.